2020
DOI: 10.1002/ecs2.3020
|View full text |Cite
|
Sign up to set email alerts
|

Plant–pollinator interactions along an urbanization gradient from cities and villages to farmland landscapes

Abstract: Urbanization affects pollinator diversity and plant–pollinator networks by changing resource availability locally and in the surrounding landscape. We experimentally established (N = 12) standardized plant communities in farmland, villages, and cities to identify the relative role of local and landscape effects on plant–pollinator communities along this urbanization gradient. We found that the number of flower visits by solitary bees, but not bumblebees, was highest in cities and lowest in farmland, with villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 41 publications
0
22
3
Order By: Relevance
“…Bee families yielded from 19 (Colletidae) to 67 (Apidae) species, and butterflies including skippers (Lepidoptera: Rhopalocera) yielded 72 species. One reason for the high syrphid richness documented may be that Southern Illinois is predominantly rural; syrphid abundance and richness have both been shown to decline with increasing urbanization (Udy et al 2020). Seventeen species (25% of total) reported in this study have not been recorded in Illinois before (Table 1), according to records in Skevington et al (2019) and 10 datasets in GBIF.org (2020d).…”
Section: Floral Associationsmentioning
confidence: 76%
“…Bee families yielded from 19 (Colletidae) to 67 (Apidae) species, and butterflies including skippers (Lepidoptera: Rhopalocera) yielded 72 species. One reason for the high syrphid richness documented may be that Southern Illinois is predominantly rural; syrphid abundance and richness have both been shown to decline with increasing urbanization (Udy et al 2020). Seventeen species (25% of total) reported in this study have not been recorded in Illinois before (Table 1), according to records in Skevington et al (2019) and 10 datasets in GBIF.org (2020d).…”
Section: Floral Associationsmentioning
confidence: 76%
“…Overall, urbanisation favours generalist species [111] and very high levels of urbanisation reduce pollinator diversity [112] (Figure 1E). Urban environments thus generally produce a network containing fewer, generalised pollinator species, with high connectance and low evenness and robustness [113,114]. This network architecture may promote pathogen transmission and infections in concert with other pressures of urban settings.…”
Section: Urbanisationmentioning
confidence: 99%
“…These network interactions can be characterised by various metrics that indicate how the network is structured and how species interact to each other (Thébault & Fontaine, 2010). A study on bee‐plant communities performed in an urbanisation gradient in Germany has demonstrated that robustness, which is a qualitative metric that represents the network resistance to species extinctions (Burgos et al ., 2007), and interaction evenness presented lower values in cities when compared to farmland and villages (Udy et al ., 2020). Another important metric, network‐level specialisation (H 2 ′) (Blüthgen et al ., 2006), presented higher values in urban sites in comparison to agricultural lands, that is insect pollinators visited proportionally fewer plant species in urban areas (Theodorou et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%